The vegetative compatibility group to which the US biocontrol agent Aspergillus flavus AF36 belongs is also endemic to Mexico - Ortega Beltran, A.; Grubisha, L.C.; Callicott, K.A.; Cotty, P.J. (Oxford University Press, 2016)
Aims: To assess frequencies of the Aspergillus flavus atoxigenic vegetative compatibility group (VCG) YV36, to which the biocontrol agent AF36 belongs, in maize-growing regions of Mexico. Methods and Results: Over 3500 A. flavus isolates recovered from maize agroecosystems in four states of Mexico during 2005 through 2008 were subjected to vegetative compatibility analyses based on nitrate nonutilizing mutants. Results revealed that 59 (1 6%) isolates belong to VCG YV36. All 59 isolates had the MAT1-2 idiomorph at the mating-type locus and the single nucleotide polymorphism in the polyketide synthase gene that confers atoxigenicity. Additional degradation of the aflatoxin gene cluster was detected in three isolates. Microsatellite loci analyses revealed low levels of genetic diversity and no linkage disequilibrium within VCG YV36. Conclusions: The VCG to which the biocontrol agent AF36 belongs, YV36, is also native to Mexico. The North American Free Trade Agreement should facilitate adoption of AF36 for use by Mexico in aflatoxin prevention programs. Significance and Impact of the Study: An USEPA registered biocontrol agent effective at preventing aflatoxin contamination of crops in the US, is also native to Mexico. This should facilitate the path to registration of AF36 as the first biopesticide for aflatoxin mitigation of maize in Mexico. Economic and health benefits to the population of Mexico should result once aflatoxin mitigation programs based on AF36 applications are implemented.